This topic contains 0 replies, has 0 voices, and was last updated by  EduGorilla 2 years, 5 months ago.

  • Author
    Posts
  • #453889 Reply
     EduGorilla 
    Keymaster
    Select Question Language :


    If y = x  –  (1/x), then x4 + x3 + 4x2  –  x + 1 = 0 becomes

    Options :-

    1. x2 (y2 + y - 2) = 0
    2. x2 (y2 + y - 3) = 0
    3. x2 (y2 + y + 6) = 0
    4. x2 (y2 + y - 6) = 0
    5. none of these
    Post your Training /Course Enquiry
    Are You looking institutes / coaching center for
    • IIT-JEE, NEET, CAT
    • Bank PO, SSC, Railways
    • Study Abroad
    Select your Training / Study category
Reply To: If y = x  –  (1/x), then x4 + x3 + 4×2  –  x + 1 = 0 becomes….
Your information:




Verify Yourself




Log in with your credentials

or    

Forgot your details?

Create Account